A New Index for the Estimation of the Aromatic Character – III - D'Auria, Maurizio (Letters in Organic Chemistry, 2014)
The energies of [π orbitals of the aromatic compounds have been collected to give an index of the aromatic character D where D = [π1Σ2n(π1-πn)]°/[π1Σ2n(π1-πn)] × a and n is the number of occupied π orbitals and a is the number of cycles in the molecule. Calculations have been performed on aromatic and heteroaromatic compounds by using DFT method at B3LYP/6-311G+(d,p) level. ERE, HOMA, the molar magnetic susceptibility (χM), and the aromatic stabilization energy (ASE) of some compounds were used to test the index. In all the cases, a good correlation has been found.
Keywords: Aromaticity